"Losers" and their mothers: Personal and political implications of poverty: James, 0 (1995) Juvenile violence in a winner-loser culture: Socio-economic and familial origins of the rise of violence against the person. London: Free Association Books. ISBN 1-85343-309-0. 164 pages - McKay, Anne (PINS-Psychology in Society, 2026)
In 1987 there was a sharp rise (40%) in juvenile violence against the person in the Britain This was at the same time as the numbers of juveniles involved in other crime dropped, and the number of young men (as a percentage of the population) also began to decrease sharply. What can explain this trend towards violence (as opposed to other forms of crime) in young people? This question is used as the focal point for a wide ranging examination of the social and familial origins of interpersonal violence. The style is reminiscent of crime thriller: we accompany the author as he tries to find out.